Mortality and pulmonary complications in patients undergoing surgery with perioperative SARS-CoV-2 infection: an international cohort study - Glasbey, JC; Li, E; Omar, OM; Simoes. JFF; Abbott, TEF; Alser, O; Arnaud, AP; Bankhead-Kendall, BK; Breen, KA; Cunha, MF; Davidson, GH; Di Saverio, S; et al. (Elsevier, 2020)
Background The impact of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on postoperative recovery needs to be understood to inform clinical decision making during and after the COVID-19 pandemic. This study reports 30-day mortality and pulmonary complication rates in patients with perioperative SARS-CoV-2 infection.